Inhibitory ingredients to protect exposed surfaces of mechanisms from rust and corrosion - A.Sobirjonov; V.M.Meliyev; RB Siddikov; Abdurahimov Lochinbek Hayitbekovich (Zien Journals, 2022)
This thesis provides information about the corrosion of metal objects and its effect on the operation of the mechanism. There is also information about the activities of anti-corrosion research institutes.
Keywords: Rust; activity; process; surface